2021
DOI: 10.3390/ijms22168700
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phospholipid/Ceramide Profiles and Eicosanoid Levels in the Plasma of Rats Irradiated with UV Rays and Treated Topically with Cannabidiol

Abstract: Chronic UV radiation causes oxidative stress and inflammation of skin and blood cells. Therefore, in this study, we assessed the effects of cannabidiol (CBD), a natural phytocannabinoid with antioxidant and anti-inflammatory properties, on the phospholipid (PL) and ceramide (CER) profiles in the plasma of nude rats irradiated with UVA/UVB and treated topically with CBD. The results obtained showed that UVA/UVB radiation increased the levels of phosphatidylcholines, lysophospholipids, and eicosanoids (PGE2, TxB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…In this context, we found that long-chain PCs that contained polyunsaturated fatty acids (PUFAs) were increased in the plant extract-treated cells, particularly PC 38:5 and PC 38:6. These data agree with the elevation of these long-chain PCs that was reported after situations of oxidative stress in [ 39 ]. By contrast, in our study, PCs with three unsaturations or less generally decreased due to the action of the Cannabis plant extracts.…”
Section: Discussionsupporting
confidence: 93%
“…In this context, we found that long-chain PCs that contained polyunsaturated fatty acids (PUFAs) were increased in the plant extract-treated cells, particularly PC 38:5 and PC 38:6. These data agree with the elevation of these long-chain PCs that was reported after situations of oxidative stress in [ 39 ]. By contrast, in our study, PCs with three unsaturations or less generally decreased due to the action of the Cannabis plant extracts.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a study presented a possible multidirectional anti-inflammatory effect of CBD after topical application in UVA/B exposure skins. Plasma samples demonstrated downregulation of relevant phospholipids (lyso-PE and lyso-PC), prostaglandin, and thromboxane, although, it also demonstrated upregulation of anti-inflammatory lipoxin (LPXA 4 ) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Deficiency of this type of ceramide may be associated with seasonal skin dryness ( 39 ). Exposure to ultraviolet irradiation can increase plasma ceramide levels and decrease SM levels in mice ( 40 ). Therefore, the level of epidermal ceramides is maintained in dynamic equilibrium by control from a number of factors and plays an important role in skin homeostasis ( 41 ).…”
Section: Ceramides In the Skinmentioning
confidence: 99%